Стосовно обертальності і зносостійкості дорожніх різців - Лукаш, В.А.; Вировець, Л.М.; Мельничук, О.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The problem of a road-cuttiny machines cutter kinematics has been analyzed. Laboratory tests have shown that the cutter can turn only at the instant it enters into or leuves the medium being broken or in cases of disappearing of or sharp decrease in axial force. Some methods to protect cutter holders from rapid wear are proposed.